2022
DOI: 10.1101/2022.07.04.498412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FOXA2 controls the anti-oxidant response in FH-deficient cells

Abstract: Hereditary Leiomyomatosis and renal cell cancer (HLRCC) is a cancer syndrome caused by inactivating germline mutations in fumarate hydratase (FH) and subsequent accumulation of fumarate. Fumarate accumulation leads to the activation of an antioxidant response by KEAP1 succination and nuclear translocation of the transcription factor NRF2. The activation of the antioxidant response is key for cellular survival in FH-deficient cells, yet the extent to which chromatin remodelling shapes the antioxidant response i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…To note, the combination of doxorubicin with NAC, the downregulation of HIF-1/PDHK1 axis was prevented (Fig 6M-N) and the metabolic shift towards oxidative metabolism was also abrogated (Fig 6O). To further demonstrate that this effect was NRF2-dependent, we use DMF (Sup Fig 7I-N), a NRF2 stabilisation agent 40 , that does not produce ROS (Sup Fig 7O). We, again, observed a similar increase in OXPHOS metabolism accompanied by the downregulation of HIF-1/PDHK1 axis (Sup Fig 7I-N).…”
Section: Resultsmentioning
confidence: 99%
“…To note, the combination of doxorubicin with NAC, the downregulation of HIF-1/PDHK1 axis was prevented (Fig 6M-N) and the metabolic shift towards oxidative metabolism was also abrogated (Fig 6O). To further demonstrate that this effect was NRF2-dependent, we use DMF (Sup Fig 7I-N), a NRF2 stabilisation agent 40 , that does not produce ROS (Sup Fig 7O). We, again, observed a similar increase in OXPHOS metabolism accompanied by the downregulation of HIF-1/PDHK1 axis (Sup Fig 7I-N).…”
Section: Resultsmentioning
confidence: 99%
“…Although the biological consequences of fumarate-dependent inhibition of histones demethylation have not been fully determined, it has been recently shown that fumarate accumulation can increase the methylation levels of H3K4, H3K27, and H3K79, inducing the activation or repression of gene transcription [77]. Consistently, a recent study has shown that FH loss modulates chromatin accessibility and allows the activation of the pioneering transcription factor FOXA2, which participates in the antioxidant response [78]. Still, further investigation is needed to understand the implications of these changes in FH-loss-associated tumorigenesis.…”
Section: Fumarate-mediatedmentioning
confidence: 89%